Transformation of education in Minangkabau: A comparation of the educational concepts of Abdullah Ahmad (1878-1933) and M. Sjafei (1893-1966) - Syafri, Ulil Amri (TAWAZUN: Jurnal Pendidikan Islam, 2024)
Education in Sumatra has been going on since the entry of Islam into Minangkabau. Through surau, education became part of the value system of Minangkabau society that succeeded in producing great scholars and santri. Surau is a typical tafaqquh fī al-dīn space in the Minangkabau realm. Along with the changes that occurred in the order of society, the role of surau as an Islamic educational institution began to fade, replaced by educational concepts from the Minangkabau renewal figures themselves. Abdullah Ahmad and M. Sjafei emerged as educational reformers in Sumatra. The concept of education developed and slowly replaced the role of surau as a place to educate the children of Nagari Minangkabau. This article tries to describe the transformation of Islamic education that occurred in Minangkabau, which is important because it became the forerunner of the transition period of colonialism and independence that affected education in the archipelago, by photographing the ideas and concepts of education of Abdullah Ahmad and M. Sjafei. The research method used is a qualitative method with a literature review approach and takes a character study analysis. The main data sources are taken from books, articles, papers, and writings that discuss the characterization of Abdullah Ahmad and M. Sjafei. This article concludes that the concept of education brought by Abdullah Ahmad became a turning point in the overall educational modernization movement in Minangkabau, especially in religious education. This movement also became the root of the change in the education model of Surau which was very monumental in the past towards the madrasa model with an academic curriculum design that was much different from the design in Surau. The education offered by M. Sjafei became a turning point in the movement of the skills education model in Minangkabau. His concept focuses on productive education that hones the talent-based skills of the nation's children. Although he does not specialize in academic education, the development of his students is still oriented towards a good religious lifestyle and religious personality, in accordance with the religious culture of the Minangkabau people. Abstrak Pendidikan di Sumatera sudah berlangsung sejak masuknya Islam ke bumi Minangkabau. Melalui surau, pendidikan menjadi bagian dari tata nilai kehidupan masyarakat Minangkabau yang berhasil melahirkan para ulama dan para santri hebat. Surau menjadi ruang tafaqquh fī al-dīn yang khas di ranah Minangkabau. Seiring dengan perubahan-perubahan yang terjadi pada tatanan masyarakatnya, peran surau sebagai lembaga pendidikan Islam mulai memudar, tergantikan dengan konsep-konsep pendidikan dari tokoh-tokoh pembaruan Minangkabau itu sendiri. Adalah Abdullah Ahmad dan M. Sjafei yang muncul sebagai tokoh pembaruan pendidikan di tanah Sumatera. Konsep pendidikannya berkembang dan perlahan menggantikan peran surau sebagai tempat mendidik anak-anak Nagari Minangkabau. Artikel ini mencoba menggambarkan transformasi pendidikan Islam yang terjadi di Minangkabau, di mana hal tersebut menjadi penting karena menjadi cikal bakal masa peralihan masa penjajahan dan kemerdekaan yang mempengaruhi pendidikan di Nusantara, dengan memotret gagasan dan konsep pendidikan Abdullah Ahmad dan M. Sjafei. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan kajian pustaka dan mengambil analisis studi tokoh. Sumber data utama diambil dari buku, artikel, makalah, dan tulisan-tulisan yang membahas tentang ketokohan Abdullah Ahmad dan M. Sjafei. Artikel ini mendapatkan kesimpulan bahwa Konsep pendidikan yang dibawa Abdullah Ahmad menjadi titik balik dalam gerakan modernisasi pendidikan secara keseluruhan di Minangkabau, khususnya pada pendidikan agama. Gerakan ini pun menjadi akar dari perubahan pendidikan model surau yang sangat monumental dahulunya menuju model madrasah dengan desain kurikulum bercorak akademik jauh berbeda dengan desain di Surau. Adapun pendidikan yang ditawarkan M. Sjafei menjadi titik balik dalam gerakan model pendidikan ketrampilan di Minangkabau. Konsepnya berfokus pada pendidikan produktif yang mengasah skill berbasis talenta anak bangsa. Meskipun ia tidak mengkhususkan diri pada pendidikan akademis, namun pembinaan para pelajarnya tetap berorientasi pada gaya hidup beragama yang baik dan berkepribadian agamis, sesuai dengan kultur budaya masyarakat Minangkabau yang agamis.